Foundational Issues in Biolinguistics - Grohmann, Kleanthes K.; Kambanaros, Maria (My University, 2021)
Biolinguistics at large takes the biological underpinnings of language seriously. This chapter outlines the basic tenets of the biolinguistic approach framed in the form of five ‘foundational questions’. While often construed with generative investigations of language, biolinguistics is not, and should not be, another term for generative grammar; the biolinguistic approach to the study of language will thus be put in a broader perspective by inspecting and dissecting the foundational questions, with particular reference to cognitive linguistics. The novelty laid out here is the regular reference to ‘macro-’ and ‘micro-cognitive’ linguistics. Finally, a specific research agenda will be singled out: language pathology in a comparative biolinguistics.